Analisis Perbandingan Laporan Keuangan untuk Menilai Kinerja Keuangan Perusahaan Konstruksi Tahun 2020-2022 : (Studi Kasus BEI) - Nur Faiza Mas’udiyah; Nilam Santika; Novia Oktaviani; Charisma Bayu Ramadhani; Meilitarizky Nanda; Cholis Hidayati (Fakultas Teknik Universitas Maritim AMNI Semarang, 2024)
Financial reports are an important instrument for companies to show company performance results. The contents of financial reports have useful benefits for both internal and external parties of the company. To find out the company's financial position, it is necessary to analyze the financial reports to see whether the company is good or bad. One way to analyze financial reports is to use ratio analysis. The aim of the research is to analyze the company's financial reports which are used to determine the size of the company. The samples used in this research were 5 companies operating in the construction sector from 2020 to 2022. The research method used was quantitative descriptive based on calculations from financial report data on the Indonesia Stock Exchange. The ratios used include liquidity ratios, activity ratio, solvency ratios and profitability ratios. The results of this research are among the five companies. Which company is the best and which company should carry out an evaluation.